Annual Report Conference on Electrical Insulation and Dielectric Phenomena
DOI: 10.1109/ceidp.2002.1048793
|View full text |Cite
|
Sign up to set email alerts
|

Towards an understanding of nanometric dielectrics

Abstract: Dielectric studies are described aimed at providing an understanding of the charge storage and transport of an epoxy resin containing TiO 2 nanoparticles. Comparative results for conventionally filled composites are given, and the results discussed in terms of the underlying physics. It is shown that nanometric fillers mitigate the interfacial polarization characteristic of conventional materials with a reduction in the internal field accumulations. Background and Vision

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
0
6

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(116 citation statements)
references
References 9 publications
5
105
0
6
Order By: Relevance
“…Nanodielectrics have attracted a great attention since the first experimental data were reported publicly in 2002 [10][11]. The current research is concentrated on the short-term breakdown and the long-term failure of epoxy and other polymer matrix with inorganic nanoparticles added.…”
Section: Introductionmentioning
confidence: 99%
“…Nanodielectrics have attracted a great attention since the first experimental data were reported publicly in 2002 [10][11]. The current research is concentrated on the short-term breakdown and the long-term failure of epoxy and other polymer matrix with inorganic nanoparticles added.…”
Section: Introductionmentioning
confidence: 99%
“…before short circuiting) and arrows show the charge decay with time. Figure 7 and Figure 8 recap the comparison made in [1] between the epoxy composites micro-and nano-filled with TiO 2 . In the nano-filled material, there is homo-charge near the electrodes whereas in the micro-filled there is hetero-charge.…”
Section: Space Charge Measurementmentioning
confidence: 99%
“…The formulation and processing of the planar specimens (having thicknesses between 500 and 750 µm) have been described previously [1]. These are cast under carefully controlled conditions to ensure good mixing, dispersion and the minimization of voids.…”
Section: Specimen Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tanaka et al recently proposed a multi-core model to explain the some high electric field phenomena in the nanocomposites [4]. Over the years, several studies on space charge characteristics in nanocomposites have been carried out [5][6][7]. It has been demonstrated that the addition of nanoparticles hinder space charge formation.…”
Section: Introductionmentioning
confidence: 99%